A violência nas lives semanais de Jair Bolsonaro - Arruda, Fernanda Fontes (2023)
Bolsonaro was elected president in 2018 and became known for his aggressive declarations in which he attacks minorities, opposition, the press, and even democracy. While in office, he used to have weekly lives on YouTube, this being an important mean of communication with his supporters. This study is justified since this form of communication between the president and his people is new and has unique characteristics that need to be understood, furthermore, when studying the violence inside this discourse it is also possible to verify how the discourse of violence is present in President Bolsonaro’s speeches and how his speech influences and is influenced by the government’s policies and in his relationship with his followers. Our general objective consists in verifying how the discourse of violence is present in President Bolsonaro’s speeches and our specific objectives are a) to identify the discursive formations present in Bolsonaro’s speeches, b) analyze the role of the violence imprint in the formation of Bolsonaro’s ethos and c) connect the violence imprints preset in his speech to his government policies. The thoughts presented here have the theoretical framework based on French Discourse Analysis and the works of Maingueneau (2013), Althuser (1983) and Bahkthin (2018) and have as main categories of analysis the ethos, and the ideological and discourse formation